THE ROLE OF MUSICAL LITERACY IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Ergash Kenjaevich Djalilov (Journals Park Publishing, 2026)
This article examines the pedagogical significance of musical literacy in preschool educational organizations, highlighting its role in the cognitive, emotional, linguistic, and social development of young children. Musical literacy is presented not only as an artistic competence but as a foundational element that strengthens auditory perception, memory, communication skills, and creativity.
Keywords: Musical literacy; preschool education; early childhood development; auditory perception; rhythm training.